Kecernaan Kalsium dan Fosfor Ransum yang mendapat Penambahan Tepung Daun Katuk (Sauropus Androgynus L. Merr), Tepung Kunyit (Curcuma Domestica) dan Kombinasinya pada Ternak Babi - Ninu, Maria Goreti; Suryani, Ni Nengah; Nenobais, Mariana (Yayasan Sumber Daya Manusia Cerdas, 2024)
The aim of this research was to determine the effect of adding katuk leaf flour (Sauropus androgynus L. Merr), turmeric flour (Curcuma domestica) and their combination in rations on consumption, calcium and phosphorus digestibility in pigs. The material used in this research were 12 pigs aged 1-2 months with a body weight range of 6-10.25 kg (KV= 19.61%). The design method used was an experimental method with a Randomized Block Design (RAK) consisting of 4 treatments and 3 groups as replications. The treatments tried were R0: Basal ration without adding katuk leaf flour and turmeric flour, R1: Basal ration + 4% katuk leaf flour, R2: Basal ration + 1% turmeric flour, R3: Basal ration + 4% katuk leaf flour + 1 % turmeric flour. The collected data was analyzed using analysis of variance (Anova). The results of analysis of variance showed that the addition of katuk leaf flour and turmeric flour in the ration had no significant effect (P>0.05) on calcium and phosphorus digestibility consumption. It was concluded that the addition of katuk leaf flour (Sauropus androgynus L. Merr) and turmeric flour (Curcuma domestica) and a mixture of the two provided the same calcium and phosphorus digestibility consumption.